2011
DOI: 10.1111/j.1349-7006.2011.01880.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic/hypoxic condition in vitro mimicking the tumor microenvironment markedly reduced the efficacy of anticancer drugs

Abstract: Tumor tissues are often hypoxic because of defective vasculature. We previously showed that tumor tissues are also often deprived of glucose. The efficacy of anticancer drugs is affected by the tumor microenvironment, partly because of the drug delivery and cellular drug resistance; however, the precise mechanisms remain to be clarified. In the present study, we attempted to clarify whether hypoglycemic ⁄ hypoxic condition, which mimics the tumor microenvironment, might induce drug resistance, and if it did, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 53 publications
2
51
0
Order By: Relevance
“…6D), we are planning to examine the synergistic effect of Emi1 knockdown in combination with other anticancer drugs that interfere with DNA synthesis. Recent study showed that the hypoxic condition induced multidrug resistance (22). Interestingly, Emi1 siRNA enhanced the sensitivity of anticancer drugs under hypoxia condition (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6D), we are planning to examine the synergistic effect of Emi1 knockdown in combination with other anticancer drugs that interfere with DNA synthesis. Recent study showed that the hypoxic condition induced multidrug resistance (22). Interestingly, Emi1 siRNA enhanced the sensitivity of anticancer drugs under hypoxia condition (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study showed that the hypoxic condition induced multidrug resistance (22). To mimic hypoxia conditions, we used cobalt chloride (CoCl 2 ).…”
Section: Emi1 Knockdown Enhances the Induction Of Apoptosis By Doxorumentioning
confidence: 99%
“…However, cells treated under these conditions were often compared to cells cultured under air, incorrectly inferring that this oxygenation was representative of "healthy" tissues, and studies have often used short-term decreases in O 2 concentration [4,5], rather than longer periods associated with disease. Additionally, air has been used to represent post-reperfusion oxygenation when modelling reperfusion events in vitro [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive literature on the effects of O 2 concentration on the efficacy of drug and radiation treatments in cancer cell killing, both in vivo and in vitro [4][5][6][7][8][9]. However, most studies have characterized these effects in vitro in cells that have been cultured, long-term, in a hyperoxic environment (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation